Genomic characterization of invasive typhoidal and non-typhoidal Salmonella in southwestern Nigeria. - Odion O Ikhimiukor; Anderson O Oaikhena; Ayorinde O Afolayan; Abayomi Fadeyi; Aderemi Kehinde; Veronica O Ogunleye; Aaron O Aboderin; Oyinlola O Oduyebo; Charles J Elikwu; Erkison Ewomazino Odih; Ifeoluwa Komolafe; Silvia Argimón; et al. (PLoS Neglected Tropical Diseases)
Background Salmonellosis causes significant morbidity and mortality in Africa. Information on lineages of invasive Salmonella circulating in Nigeria is sparse. Methods Salmonella enterica isolated from blood (n = 60) and cerebrospinal fluid (CSF, n = 3) between 2016 and 2020 from five tertiary hospitals in southwest Nigeria were antimicrobial susceptibility-tested and Illumina-sequenced. Genomes were analysed using publicly-available bioinformatic tools. Results Isolates and sequence types (STs) from blood were S. Typhi [ST1, n = 1 and ST2, n = 43] and invasive non-typhoidal Salmonella (iNTS) (S. Enteritidis [ST11, n = 7], S. Durham [ST10, n = 2], S. Rissen [ST8756, n = 2], S. Chester [ST2063, n = 1], S. Dublin [ST10, n = 1], S. Infantis [ST603, n = 1], S. Telelkebir [ST8757, n = 1] and S. Typhimurium [ST313, n = 1]). S. Typhi ST2 (n = 2) and S. Adabraka ST8757 (n = 1) were recovered from CSF. Most S. Typhi belonged to genotype 3.1.1 (n = 44), carried an IncY plasmid, had several antibiotic resistance genes (ARGs) including blaTEM-1 (n = 38), aph(6)-Id (n = 32), tet(A) (n = 33), sul2 (n = 32), dfrA14 (n = 30) as well as quinolone resistance-conferring gyrA_S83Y single-nucleotide polymorphisms (n = 37). All S. Enteritidis harboured aph(3")-Ib, blaTEM-1, catA1, dfrA7, sul1, sul2, tet(B) genes, and a single ARG, qnrB19, was detected in S. Telelkebir. Typhoidal toxins cdtB, pltA and pltB were detected in S. Typhi, Rissen, Chester, and Telelkebir. Conclusion Most invasive salmonelloses in southwest Nigeria are vaccine-preventable infections due to multidrug-resistant, West African dominant S. Typhi lineage 3.1.1. Invasive NTS serovars, including some harbouring typhoidal toxin or resistance genes, represented a third of the isolates emphasizing the need for better diagnosis and surveillance.